1984
DOI: 10.3354/meps014207
|View full text |Cite
|
Sign up to set email alerts
|

Detection of glutamine synthetase activity in marine phytoplankton: optimization of the biosynthetic assay

Abstract: A comprehensive study of the key ammonium-assimilating enzyme, glutarnine synthetase (GS), was made in a variety of marine phytoplankton. GS activity was detected in 13 out of the 15 species examined comprising 6 algal classes. Both the biosynthetic GS reaction as well as the transferase reaction were measured with phytoplankton extracts for comparative purposes. In evaluating the differences between the 2 assays it was found that the biosynthetic assay was more sensitive than the transferase assay in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

1986
1986
1996
1996

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 23 publications
1
32
0
2
Order By: Relevance
“…In subsequent studies with the diatom Skeletonerna costaturn Dortch et al (1979) concluded that GDH could account for less than 5 % of the NH: uptake and assimilation rates in cells. An ensuing examination of 13 marine phytoplankton species comprising 6 algal classes revealed the presence of the GS enzyme with much greater affinities for NH: (ca 2 to 8 FM) (Bressler & Ahmed 1984). Therefore, the occurrence of a highly efficient NH: assimilating enzyme system (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In subsequent studies with the diatom Skeletonerna costaturn Dortch et al (1979) concluded that GDH could account for less than 5 % of the NH: uptake and assimilation rates in cells. An ensuing examination of 13 marine phytoplankton species comprising 6 algal classes revealed the presence of the GS enzyme with much greater affinities for NH: (ca 2 to 8 FM) (Bressler & Ahmed 1984). Therefore, the occurrence of a highly efficient NH: assimilating enzyme system (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The NH: derived from either NO; andlor NO; reduction or direct uptake from the extracellular medium is then assimilated into amino acids. The specific pathway for this latter assimilation step has been the subject of considerable speculation, with the current consensus favoring a coupled enzymatic reaction involving glutamine synthetase (GS) and glutamate synthase (GOGAT) (Morris 1974, Ahmed et al 1977, Miflin & Lea 1980, Syrett 1981, Wheeler 1983, Falkowslu 1983, Bressler & Ahmed 1984. Both the phylogenetic occurrence of GS and sensitive assay methods for ~t s detection have been documented for a variety of phytoplankton species (Bressler & Ahmed 1984, Clayton & Ahmed unpubl.).…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of cell-free extracts from experimental phytoplankton cultures is described in Bressler & Ahmed (1984). Briefly, a volume of phytoplankton culture was filtered onto a glass fiber filter.…”
Section: Methodsmentioning
confidence: 99%
“…Shapiro & Stadtman 1970, Falkowski & Rivkin 1976, Bressler & Ahmed 1984 or detection of the ADP end product using a fluorometric coupled enzyme assay (Falkowski & Rivkin 1976). Both approaches have limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation